Survei Kondisi Fisik Peserta Kegiatan Ekstrakurikuler Bolabasket - Valentino, Andreano Febrio; Nurrochmah, Siti (Universitas Negeri Malang, 2020)
Abstract: The purpose of this study was to determine the ability of the physical condition of the male and female groups participating in basketball extracurricular activities at the Santo Albertus High School, Malang City. The research design used a survey design. The results of the research on the chest pass medicine ball test and the vertical jump test for the male group were in the moderate category, the 20-meter running test, the Illinois test, and the vertical jump test for the female group were in the moderate and poor category. Conclusion from the research results there are still tests that have below good criteria.Â Abstrak: Tujuan penelitian ini yaitu untuk mengetahui kemampuan kondisi fisik kelompok putra dan putri peserta kegiatan ekstrakurikuler bolabasket di SMAK Santo Albertus Kota Malang. Rancangan penelitian menggunakan rancangan survei. Hasil penelitian pada tes chest pass bola medicine dan tes vertical jump untuk kelompok putra termasuk dalam kategori cukup, pada jenis tes lari 20 meter, tes illinois, dan tes vertical jump untuk kelompok putri termasuk dalam kategori cukup dan kurang baik. Simpulan dari hasil penelitian masih ada tes yang mempunyai kriteria dibawah baik.